Detection of acoustic signals from Distributed Acoustic Sensor data with Random Matrix Theory and their classification using Machine Learning - (:unkn) unknown (SPIE-INT SOC OPTICAL ENGINEERING, 2020)
This work aims at the detection and classification of Distributed Acoustic Sensor (DAS) acquired acoustic signals. We obtained the data by probing an optical fiber with light pulses and gauging the Rayleigh backscatter. Said data contains four different classes; Walking, Shovel and Pick digging as well as Hammer hitting. We first proceed by detecting the event and its location along the fiber and extracting it from the random noise using Spiked Random Matrix Theory (RMT) models, namely Marchenko-Pastur (MP) and Tracy-Widom (TW) distributions. We then label the datasets accordingly and proceed with the classification process using machine learning algorithms. For this, we test and evaluate Convolutional Neural Networks (CNN), which has been proven to provide high accuracies in similar studies, taking the spectrograms of the signals as our network's input. We conclude by providing the performance of our CNN architecture and propose a few options to further improve the performance of the model.
Keywords: Distributed Acoustic Sensing; Random Matrix Theory; Event Classification; Machine Learning; Fiber Optic Sensing; Convolutional Neural Network